Load characteristics, in vitro bioaccessibility and health risk assessment of PM2.5–bounded heavy metals in indoor air of waterpipe and/ or cigarette cafes compared to smoking-free cafes. Issue 1 (1st January 2020) - Masjedi, Mohammad Reza; Taghizadeh, Farhad; HamzehAli, Sanaz; Ghaffari, Sonia; Ahmadi, Ehsan; Dobaradaran, Sina; Ramavandi, Bahman; Tahergorabi, Mahsa; Arfaeinia, Hossein
ABSTRACT: Samples of PM2.5 particulates were collected from indoor air of 36 cafés, 14 cafés in which only water pipe (WS) was used, eight in which only cigarette was smoked (CC), six in which both waterpipe and cigarette were smoked (WCC), and eight cafés in which no smoking occurred (SFC) in Tehran. After that, the concentration of lead (Pb), cadmium (Cd), nickel(Ni), and chromium (Cr) was examined by atomic absorption spectrophotometer (AAS) (GF 5000, Australia). The results indicated that the ƩMetal concentration (Mean ±SD) in WCC, WC, CC, and SFC cafés were 1118.5±50.42, 663.64±40.79, 425.57±17.55, and 79.02±5.13 ng/m3, respectively. The mean bioaccessibility of Pb, Cr, Ni, and Cd was obtained as 39.7, 31.4, 7.35, and 74.6%, respectively. The results of risk assessment indicated that exposure to heavy metals in the indoor air of smoking cafés of Tehran is considered high.